Association of diabetes mellitus and high myopia in primary open angle glaucoma - Bhattarai, S; Sapkota, K; Prabhudesai, SMN; Shrestha, JK; Sharma, AK (Health Renaissance, 2012)
Background: Primary open angle glaucoma (POAG), a chronic, slowly progressive, optic neuropathy, is insidious in onset and painless, until it has caused a significant loss of vision and visual field. Diabetes mellitus and high myopia are the major risk factor of POAG. Objectives: To determine correlation of diabetes mellitus and high myopia in POAG and to estimate the duration of onset of POAG from the diagnosis of diabetes mellitus and high myopia. Method: This retrospective and cross sectional study was conducted in Prabhudesai eye clinic, Pune, India. All the patients diagnosed as POAG from 1st September 2008 to 1st March 2009 AD were included in this study. Association of high myopia with diabetes mellitus was determined by SPSS 13 software. The average duration of onset of POAG after the diagnosis of diabetes mellitus and high myopia was calculated. Results: There were 63.3% (38) male and 36.7% (22) female out of 60 patients of POAG with mean age 54.4±15.4 years. Among them, 27 (45.0%) patients had diabetes mellitus or high myopia. Onset of POAG was found to occur after 11.1±8.3 years of the diagnosis of diabetes and 10.6±3.2 years after the diagnosis of high myopia. Conclusion: The incidence of diabetes mellitus and high myopia was high and significantly associated in primary open angle glaucoma. POAG was detected soon after the onset of diabetes mellitus and high myopia. DOI: http://dx.doi.org/10.3126/hren.v10i1.6005 HREN 2012; 10(1): 35-39